2008
DOI: 10.1093/ajcn/88.1.203
|View full text |Cite
|
Sign up to set email alerts
|

Markers of dietary fat quality and fatty acid desaturation as predictors of total and cardiovascular mortality: a population-based prospective study

Abstract: Altered endogenous FA desaturation might contribute to mortality risk because we observed independent associations between desaturase activity indexes and mortality. The proportion of linoleic acid was inversely related, and FAs reflecting saturated fat intake were directly related to mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
236
3
9

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 239 publications
(284 citation statements)
references
References 60 publications
36
236
3
9
Order By: Relevance
“…On the other hand, our studies show that over-consumption of saturated FAs is associated with the presence and extent of carotid plaque (78) and with other CVD risk factors such as glucose intolerance (59,67,82), blood pressure (67,77) and elevated heart rate (83,84). These findings support the prospective studies by Vessby's group in Sweden that recently showed a direct link between serum levels of the saturated myristic and palmitic FAs and cardiovascular mortality (89).…”
Section: Coronary Heart Diseasesupporting
confidence: 88%
“…On the other hand, our studies show that over-consumption of saturated FAs is associated with the presence and extent of carotid plaque (78) and with other CVD risk factors such as glucose intolerance (59,67,82), blood pressure (67,77) and elevated heart rate (83,84). These findings support the prospective studies by Vessby's group in Sweden that recently showed a direct link between serum levels of the saturated myristic and palmitic FAs and cardiovascular mortality (89).…”
Section: Coronary Heart Diseasesupporting
confidence: 88%
“…On the other hand, changes in saturated and monounsaturated fatty acids with respect to insulin resistance were lipoprotein-specific. Epidemiological prospective studies have shown that high proportions of esterified palmitic and stearic, and low proportions of esterified linoleic fatty acids in serum are risk factors for type 2 diabetes [33][34][35], myocardial infarction [36,37], the metabolic syndrome [38] and overall and cardiovascular mortality [39]. The relationship between the amount of polyunsaturated fat in the diet and the respective proportions of serum esterified polyunsaturated fatty acids is strong [40,10].…”
Section: Discussionmentioning
confidence: 99%
“…As such studies can only identify associations and cannot elucidate mechanisms, the same concerns have been raised in relation to the relationship between dietary fat type and CVD risk. Warensjö et al (2008) identified that many intervention studies looking at this relationship have been of too short duration, too underpowered and have often failed to adequately assess intakes of individual fatty acids. Gibson et al (2009) reviewed the evidence from cohort studies in relation to dairy foods and coronary heart disease (CHD) and concluded that there was no consistent evidence that dairy food consumption was associated with higher risk of CHD.…”
Section: Milk Dairy Products and Chronic Diseasementioning
confidence: 99%